2016
DOI: 10.15287/afr.2016.544
|View full text |Cite
|
Sign up to set email alerts
|

Effects of common oak (Quercus robur L.) defolition on the soil properties of an oak forest in Western Plain of Romania

Abstract: Abstract. This study was conducted to evaluate the variability of the chemical properties of the soil of an oak forest affected by defoliation and the corresponding microbial abundance. Soil samples were collected from a control zone (zone 1) without outbreaks of defoliating insects and from a sample zone (zone 2) where the trees were affected by Lymantria dispar L. defoliation. The research was conducted to determine the changed conditions for soil microorganisms produced as a consequence of defoliation. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Consequently, studying the effects of chemical/organic fertilizers on the natural microbial community is of crucial importance. For example, understanding how NPK chemical fertilizers influence the microbial biomass, which is an indicator of soil fertility and quality, is a basic prerequisite for understanding microbiological processes [63], in order to preserve the ecosystem functions of soil.…”
Section: Biosolidsmentioning
confidence: 99%
“…Consequently, studying the effects of chemical/organic fertilizers on the natural microbial community is of crucial importance. For example, understanding how NPK chemical fertilizers influence the microbial biomass, which is an indicator of soil fertility and quality, is a basic prerequisite for understanding microbiological processes [63], in order to preserve the ecosystem functions of soil.…”
Section: Biosolidsmentioning
confidence: 99%
“…While bacterial growth decreases following N fertilization or N deposition owing to C limitation (e.g., References [14,15]), the input of labile C compounds increases bacterial and fungal populations [6,16]. For example, oak (Quercus robur L.) defoliation by the gypsy moth (Lymantria dispar L.) led to increased populations of fungi and N 2 -fixing bacteria in soil [17]. Increased populations of culturable fungi and Actinobacteria were found in pine forests (Pinus sylvestris L.) defoliated by the pine beauty moth (Panolis flammea D. et S.) and the pine-tree lappet (Dendrolimus pini L.) [6].…”
Section: Introductionmentioning
confidence: 99%
“…Along with a change in vegetation regeneration in the defoliated forest, a decrease in root biomass and root exudates of labile C in the topsoil can also shift the microbial communities associated with roots, as illustrated by a negative correlation between herbivory and ectomycchorizal fungi abundance [13,60]. Other studies have suggested higher soil acidity [27] or lower C: N ratio in the litterfall [17] could increase fungal biomass in topsoil under defoliated trees compared to undefoliated trees, but our fungal ratio indicator remained constant between undefoliated and defoliated sites. This possible change in forest regeneration at our site favouring balsam fir over trembling aspen may also have consequences for soil micronutrients.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Castaño et al (2020) found a decrease in soil fungal biomass associated with a decrease in root exudates after an outbreak by the pine processionary moth. In lab cultures, Oneț et al (2016) found an increase in fungi and a decrease in heterotrophic bacteria from soils sampled under oaks defoliated by spongy moth and attributed them to higher pH and changes in soil chemistry.…”
Section: Introductionmentioning
confidence: 99%